Sex-Biased CD3ζ 3ʹ-UTR SNP Increased Incidence Risk in Aplastic Anemia - Guo L; Zhang Y; Liu X; Xiao Y; Luo W; Fang S; Li Y; Lai J; Li Y; Li B (International Journal of General Medicine)
Lixing Guo,1,* Yuping Zhang,2,* Xiaoen Liu,3,* Yankai Xiao,3,* Weifeng Luo,4 Su Fang,5 Yan Li,6 Jing Lai,7 Yangqiu Li,3,7 Bo Li3 1Department of Hematology and Oncology, The Fifth Affiliated Hospital of Jinan University, Heyuan, People’s Republic of China; 2Department of Hematology, Guangzhou First People’s Hospital, The Second Affiliated Hospital of South China University of Technology, Guangzhou, People’s Republic of China; 3Institute of Hematology, School of Medicine, Jinan University, Guangzhou, People’s Republic of China; 4Department of Management, Guangzhou Blood Center, Guangzhou, People’s Republic of China; 5Institute of Hematology, Xi’an Children’s Hospital, Xi’an, People’s Republic of China; 6Department of Cardiology, First Affiliated Hospital, Jinan University, Guangzhou, People’s Republic of China; 7Department of Hematology, First Affiliated Hospital, Jinan University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yangqiu Li; Bo Li, Email yangqiuli@hotmail.com; jnlibo517@163.comPurpose: Aplastic anemia (AA) is a bone marrow failure syndrome with an unclear pathogenesis. Abnormal T cell immunity is one of the mechanisms involved in AA, and CD3ζ is an important signaling molecule for T cell activation. Single-nucleotide polymorphisms (SNPs) in CD3ζ 3ʹ-untranslated region (3ʹ-UTR) were associated with some immune-related disease occurrence and affect CD3ζ protein level. In this study, our aim was to analyze whether CD3ζ 3ʹ-UTR SNPs were associated with AA susceptibility and had influence on CD3ζ protein level and provide new research data for exploring the pathogenesis of aplastic anemia.Patients and Methods: We screened the genotypes of SNPs in 101 healthy individuals and 91 AA patients by PCR-RFLP and sequencing. In addition, the effect of specific CD3ζ 3ʹ-UTR SNPs was analyzed by flow cytometry and dual luciferase assay.Results: Four SNPs of CD3ζ 3ʹ-UTR, 1184 C >G (rs3738212), 1292 delG (rs3831958), 1403 G >C (rs1052230) and 1410 A >T (rs1052231) were identified from Chinese healthy individuals and AA patients in which rs3738212 was not previously reported. Increased risk of AA was observed in female AA who with heterozygous genotype of linkage disequilibrium SNP (rs3831958, rs1052230 and rs1052231). Different genotypes of rs3738212 have sex-biases feature in AA, higher 1184 CC frequency in male AA and higher 1184 CG frequency in female AA. Furthermore, rs3738212 could upregulate CD3ζ protein level.Conclusion: This study first identified sex-specific CD3ζ 3ʹ-UTR SNPs that were associated with risk of AA. Our data also demonstrated that rs3738212 could upregulate CD3ζ protein level.Keywords: aplastic anemia, CD3ζ 3ʹ-untranslated region, single-nucleotide polymorphisms, CD3ζ protein level